ChemInform Abstract: 2‐Arylacetic Anhydrides as Ammonium Enolate Precursors. Issue 27 (8th July 2014) - Morrill, Louis C.; Ledingham, Lyndsay A.; Couturier, Jean‐Philippe; Bickel, Jasmine; Harper, Andrew D.; Fallan, Charlene; Smith, Andrew D.
Abstract Readily prepared 2‐arylacetic anhydrides (I) act as convenient ammonium enolate precursors in isothiourea‐mediated catalytic asymmetric intermolecular Michael addition‐lactonization processes.